Analysis of PAHs (polycyclic aromatic hydrocarbons) and other main components in black crusts collected from the Monumental Cemetery of Milan (Italy). Issue 1 (1st April 2022) - Ricciardi, M.; Faggiano, A.; Pironti, C.; Motta, O.; Carotenuto, M.; Comite, V.; Fermo, P.; Proto, A.
Abstract: The present work focuses on the chemical characterization of some chemical components present in black crusts collected from the Monumental Cemetery of Milan located in the homonymous city (Northern Italy). Samples of black crusts, recovered over two sampling campaigns, were analysed by using X-ray Diffraction and Fourier Transform-Infrared spectroscopy. Moreover, Ionic chromatography analyses were performed on water extracts of the black crust samples, while High Performance Liquid Chromatography measurements were carried out on dichloromethane/pentane extracts. This approach was used with the aim to identify the presence of polycyclic aromatic hydrocarbons (PAHs) in these black crusts and the pollution sources responsible for their formation. The knowledge of the pollution sources responsible for the degradation phenomena occurring on cultural heritages, such as black crust formation, is fundamental for the identification of proper preservation strategies, as well as for the development of emission reduction policies on a local scale.